SAP Next-Gen Innovation with Purpose - Welz, Bernd (Springer International Publishing, 2018)
This book presents SAP Next-Gen, an innovation community for SAP Leonardo. It is intended for next generation business leaders, Chief Digital Officers, Chief Innovation Officers, Chief Information Officers and IT professionals who are defining the vision, strategy, technologies and organizational changes needed to drive their exponential enterprise and to innovate with purpose. The book opens with an introduction to turning bold ideas into reality with a purpose-driven mindset supporting the 17 United Nations Global Goals. Part 1 focuses on what's at stake including Digital - The New Normal, Exponential Growth, and Innovation in the 21st century. Part 2 introduces readers to the SAP Next-Gen matchmaking model, and readers are invited to join SAP Next-Gen clubs for industries, technologies, and methodologies. Readers also learn about the Silicon Valleys of the world, make vs. buy vs. join, and where to learn more and get engaged with SAP Next-Gen. SAP Next-Gen is an innovation community for SAP Leonardo supporting SAP's 355,000+ customers across 25 industries in 180+ countries. SAP Next-Gen enables customers and partners to connect with academic thought leaders, researchers, and students in the SAP Next-Gen network of 3,200+ educational institutions across 111 countries worldwide, as well as with startups, tech community partners, venture firms, purpose driven partners, and SAP experts. .